Importance of measuring Fractional Exhaled Nitric Oxide (FeNO) in the management of asthma - Mamun, SM AA; Haque, Ziaul; Jahan, Rowshne; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2022)
Asthma is characterized by chronic airway inflammation leading to respiratory symptoms (dyspnea, wheezing, chest tightness and cough). So direct measure of the level of inflammation can be of paramount importance in the proper understanding of severity of asthma. Nitric oxide (NO) isa product of inflammation in the airways and an important regulator of immune responses that is overproduced in asthma. For this purpose, the measurement of Fractional Exhaled Nitric Oxide (FeNO) has been used since the early years of the current century as a non-invasive, easy-to-assess tool useful for diagnosing and managing asthma. In this narrative review we extended our effort to explain the usefulness of FeNO as a predictor of response to inhaled corticosteroids (ICSs), to monitor adherence and as a diagnostic tool in asthma management. Bangladesh J Medicine 2022; 33: 241-246